Exploring the role of Chinese herbal medicine in the long-term management of postoperative ovarian endometriotic cysts: a systematic review and meta-analysis - Ding, Danni; Liu, Shaoxuan; Liu, Fangyuan; Hao, Songli; Zhang, Chunlan; Shen, Ying; Wei, Wei; Chen, Qiaochu; Han, Fengjuan (Frontiers in Pharmacology, 2024)
Background Ovarian endometriotic cysts (OEC) represent the primary manifestation of endometriosis, constituting a hormonally dependent inflammatory disorder in gynecology. It significantly affects the quality of life and reproductive health of women. It is worth noting that traditional Chinese medicine (TCM), especially Chinese herbal medicine (CHM), has been widely applied in mainland China due to its unique therapeutic system and commendable clinical efficacy, bringing new hope for preventing and managing OEC. Objective This study aims to evaluate the efficacy and safety of CHM in the management of postoperative OEC. Simultaneously, it seeks to explore the medication laws, therapeutic principles, and specific treatment mechanisms of CHM. Methods Eight electronic databases were searched from their inception to 01 November 2023. Randomized controlled trials (RCTs) assessing the therapeutic effects and safety of CHM for postoperative OEC were included. The risk of bias for each trial was assessed using the Cochrane Collaboration’s tool. The certainty of the evidence was evaluated using the GRADE profiler 3.2. Additionally, we extracted formulation from the included studies, conducting a thorough analysis. Results (ⅰ) Twenty-two RCTs involving 1938 patients were included. In terms of the primary efficacy outcome, the CHM group demonstrated a potentially lower recurrence rate compared to both control (odds ratio (OR) = 0.25; 95% confidence intervals (CI): 0.10–0.64) and conventional western medicine (CWM) (OR = 0.26; 95% CI: 0.11–0.65) groups. Furthermore, the joint application of CHM and CWM resulted in a significant reduction in the recurrence rate (OR = 0.26; 95% CI: 0.17–0.40). (ⅱ) Regarding secondary efficacy outcomes, (a) Total clinical efficacy rate: CHM showcased an augmentation in clinical effectiveness compared to both the control (OR = 4.23; 95% CI: 1.12–15.99) and CWM (OR = 2.94; 95% CI: 1.34–6.43) groups. The combined administration of CHM and CWM substantially enhanced overall clinical effectiveness (OR = 3.44; 95% CI: 2.37–5.00). (b) VAS Score: CHM exhibited the capacity to diminish the VAS score in comparison to surgery alone (Mean difference (MD) = −0.86; 95% CI: -1.01 to −0.71). Nevertheless, no substantial advantage was observed compared to CWM alone (MD = −0.16; 95% CI: -0.49 to 0.17). The integration of CHM with CWM effectively ameliorated pain symptoms (MD = −0.87; 95% CI: -1.10 to −0.65). (c) Serum Level of Cancer antigen 125 (CA125): the CHM group potentially exhibited lower CA125 levels in comparison to CWM alone (MD = −11.08; 95% CI: -21.75 to −0.42). The combined intervention of CHM and CWM significantly decreased CA125 levels (MD = −5.31; 95% CI: -7.27 to −3.36). (d) Pregnancy Rate: CHM exhibited superiority in enhancing the pregnancy rate compared to surgery (OR = 3.95; 95% CI: 1.60–9.74) or CWM alone (OR = 3.31; 95% CI: 1.40–7.83). The combined utilization of CHM and CWM demonstrated the potential to enhance pregnancy rates compared to CWM (OR = 2.99; 95% CI: 1.28–6.98). Concerning safety outcome indicators, CHM effectively decreased the overall incidence of adverse events and, to a certain extent, alleviated perimenopausal symptoms as well as liver function impairment. (ⅲ) Most of CHMs were originated from classical Chinese herbal formulas. Prunus persica (L.) Batsch (Taoren), Angelica sinensis (Oliv.) Diels (Danggui), Salvia miltiorrhiza Bunge (Danshen), Paeonia lactiflora Pall. (Chishao), and Corydalis yanhusuo W.T.Wang (Yanhusuo) were most frequently used CHM. Conclusion CHM may be a viable choice in the long-term management of postoperative OEC, with the potential to enhance clinical efficacy while decreasing recurrence and adverse effects.